The role of a residential placement in preparing children for placement with a foster family - Cliona Murphy (Scottish Journal of Residential Child Care)
Placement in residential care is one element of the Lisdeel Family Placement Initiative. Children referred to the Initiative stay in a residential placement in Lisdeel House for a number of months, while a range of interventions is combined to prepare the child for living with a foster family. This paper details the role of the preparatory residential placement, and the roles of those service providers involved in the preparatory process.